The Emergence of di.kud.gal in Ur.ra5 = ḫubullu 2: Textual Development and Cultural History - Chike, Julian C. (JAOS, 2025)
Ur.ra5 = ḫubullu was one of the central pillars of Mesopotamia’s cuneiform lexical tradition. Over several centuries, these lexical lists were transmitted from Nippur to various regions in the ancient Near East (Kiš, Sultantepe, Emar, Alalah, Ugarit, Hattuša, Hazor, Askelon, and Amarna). Along with appreciable overlap, there is noticeable variation among them. Although some scholars have explained the variations quantitatively, there has been minimal explanation of the variations qualitatively. I examine one specific variation in Ur.ra5 = ḫubullu—viz., the emergence of multiple di.kud.gal entries and associated variant Akkadian translations in the second chapter division. Why did later versions incorporate multiple entries as opposed to just one? Furthermore, why did later scribes associate di.kud.gal with different Akkadian terms? Lastly, what does tracing this textual development reveal about the di.kud.gal category of leadership prior to the first millennium BCE? To answer these questions, I triangulate data from Ur.ra5 = ḫubullu 2, textual finds from the land of Hana, and a series of sociopolitical shifts that occurred along the Middle Euphrates during the late Old Babylonian and Middle Babylonian periods.